A política de assistência social em Foz do Iguaçu e os imigrantes: um diálogo necessário - Gramkow, Cristina (2022)
The search for services, benefits, programs and social projects for family care is the main demand from users of the Social Assistance Reference Centers (SARC), generally consisting of a socially and economically vulnerable population. In the case of immigrants, the risk of vulnerability can be aggravated, with social services being the only alternative once they find themselves in an unknown country, without a family support network that can help them face the problems they are experiencing. The present research, of an exploratory, cross-sectional nature, aimed to analyze aspects of the social assistance policy of Foz do Iguaçu/PR and the access to social benefits by immigrants living in the city. Structurally, the study was conceived in two moments; a first one of quantitative approach, considering secondary data and information provided by the Secretariat of Social Assistance and SARCs of the municipality of Foz do Iguaçu/PR. The second moment of qualitative approach, consisted of a field research with interviews with ten resident immigrants and users of SARCs. The quantitative data were systematized in Microsoft Excel spreadsheet, and a simple descriptive statistical analysis was performed. Qualitative data were systematized and analyzed according to the Thematic Dialogic Analysis, emerging four analytical categories: 1) reasons and motivations for immigration; 2) social assistance services for immigrants in Foz do Iguaçu; 3) access to social benefits by immigrants and; 4) vulnerabilities of the immigrant. The critical perspective, oriented by Dialectical Historical Materialism, was the reference for the analysis, with the category of social inequality playing a central role. The results revealed the scarcity of records in the social welfare services of the municipality that allow us to identify the demand of the immigrant public and the services provided in SARC for this specific population. Through the Unified Registry, we identified people from 58 ethnic groups, totaling 4,442 foreigners. The largest number of registrations (n=2,609) and of people benefited by Bolsa Familia (n=1,450) were people from Paraguay and Venezuela with 622 registrations and 278 beneficiaries of Bolsa Família. Argentines with 261 registrations and 158 beneficiaries, Colombians 216 registrations and 186 beneficiaries, and Haitians with 122 registrations and 100 beneficiaries. In the field research, it was observed that the migratory process was triggered by economic, social and political problems in the case of Venezuelans, for work in the case of Paraguayans, for studies by Haitians, and by family choice in the case of Argentines. Their insertion in the labor market was incompatible with the academic and professional training acquired in their country of origin, with lower salaries than those paid by Brazilians and with precarious working conditions. The research allowed us to know relevant aspects of the reality of immigrants, indicating the need for future research that considers the pre-pandemic, pandemic and post-pandemic period to identify fluctuations in the demand for social assistance services, as well as the improvement of registration systems of social assistance services that allow us to identify the demand and the assistance provided to foreigners, especially because it is a border region.